Handbook of measurements benchmarks for systems accuracy and precision - Badiru, Adedeji Bodunde 1952-; Racz, LeeAnn (Industrial innovation series, 2016)
"Planning, measuring, and paying attention to details form the basis for all successful engineering operations. Measurements pervade everything we do and must be viewed from a systems perspective. A comprehensive all-encompassing guide to measurements, Handbook of Measurements: Benchmarks for Systems Accuracy and Precision focuses on high-level engineering computations essential for benchmarks and technical innovation. The book uses a systems framework and a technically rigorous approach to systems linking of measurements--an approach that sets it apart from other handbooks. The popular saying "measure twice and cut once" bears out the importance of measurements in human endeavors. This handbook covers both qualitative and quantitative topics of measurement. It opens with a chapter on the fundamentals of measurement and includes coverage of human-centric measurements, such as measurement of personnel productivity and contractor performance. It concludes with three appendices on measurement, references, conversion factors, equations, formulas, and statistics for measurement. It is well understood that humans cannot manage anything that cannot be measured. All elements involved in our day-to-day decision making involve some form of measurement, whether in the kitchen, retail, sports, service operations, geographical exploration, health care delivery, worker productivity, clothing design, engineering product design, or space craft launching. Measuring an attribute of a system and then analyzing it against some standard, some specification, some best practice, or some benchmark empower a decision maker to take appropriate and timely actions. This book gives you a guide for sustainable practices to ensure accurate measurements, helping you make decisions backed by metrics." -- Publisher's description